Development of tense and aspect systems - Gvozdanović, Jadranka (Benjamins current topics, 2022)
"Linguistic construal of time lies at the center of language and language use; it is also one of the cognitive foundations of culture. The focus of the papers in this volume is on historical developments of genetically different aspect and tense systems across continents, with contributions on the Sogeram languages of Papua New Guinea, the Arandic languages of Australia, Kisikongo Bantu, and Japanese. In addition, two prototypical Indo-European tense-aspect systems, those of Vedic and Latin, are analyzed in a comparative perspective. Across language groups and continents, the general principles revealed by the studies presented here contribute towards a novel and deepening understanding of tense and aspect. They contribute not only to modelling and theory, but also to a better understanding of processes in individual languages. Originally published as special issue of the Journal of Historical Linguistics 10:2 (2020)"--
"These materials were previously published in Journal of historial linguistics 10:2 (2020)."
Includes bibliographical references
Keywords: Aufsatzsammlung